From Start-to-Finish: A Partnership With Advanced Practice Providers in Tele-Consultation Within Pediatric Urology - Crigger, Chad; Sholklapper, Tamir; Mitchell, Katharina; Eckert, Kristie; Zupper, Shirley; Bartlett, Megan; Ost, Michael C.; Al-Omar, Osama (Frontiers in Urology, 2022)
Background Telemedicine is commonplace and accepted for delivering health care due to the coronavirus pandemic. It has proven useful in increasing access to traditionally limited subspecialties and bridged the gap of locoregional geographic restraints. We report a follow up of our experience building tele-consultation capacity for pediatric urology in a resource constrained area. Methods After IRB approval (IRB# 1910741113), patients were prospectively recruited for tele-consultation encounters with a tertiary academic center between August 2018 and March 2020 (pre-dating the coronavirus pandemic). Advanced practice providers (APPs) received additional training in physical diagnosis and examination before returning to satellite clinics in their communities and facilitating tele-consultation with an academic pediatric urologist. Postoperative outcomes were analyzed out to eight weeks and any peri- and postoperative complications were assessed using the Clavien-Dindo classification system. Finally, anonymous surveys were administered to the APPs at the conclusion of the recruitment period to assess their satisfaction with telemedicine clinics and perceived barriers to implementation. Results 92 tele-consultation encounters took place between August 2018 and March 2020. The most common reasons for presentation were undescended testis (UDT) (n=15), urinary tract infection (n=13) and enuresis (n=13). The most common surgical case booked by the APPs in the satellite clinic was orchiopexy (n=10). Mean distance travel saved was 299.8 miles. In 23 patients who were schedule surgery, only two patients (8.7%) had an initial diagnosis that differed with their APP pre-operative diagnosis. Of the 22 patients who underwent surgery, all elected virtual visits for postoperative evaluation. No patient experienced complications. Initial consultations averaged 14 minutes (range 9-20 minutes), while mean duration of postoperative evaluations was 9 minutes (range 6-13 minutes). With regards to surveys, APPs reported an overall positive experience with tele-consultation (4.5/5, n=7) and all planned on incorporating it into their future practice (4.9/5, n =7). Conclusion A hybrid tele-consultation video conferencing clinic with heavy reliance on APPs is a safe, reliable and economical way to address pediatric subspecialty surgical needs in the rural setting. With proper training and exposure, APPs can safely perform preoperative assessments and correctly refer patients for surgical intervention, adding efficiency to surgical subspecialty workflow.